2022
DOI: 10.3389/fcimb.2022.906563
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antifungal Activity of Ibrexafungerp (SCY-078) Against Contemporary Blood Isolates From Medically Relevant Species of Candida: A European Study

Abstract: BackgroundIbrexafungerp (SCY-078) is the newest oral and intravenous antifungal drug with broad activity, currently undergoing clinical trials for invasive candidiasis.ObjectiveThe aim of this study was to assess the in vitro activity of ibrexafungerp and comparators against a collection of 434 European blood isolates of Candida.MethodsIbrexafungerp, caspofungin, fluconazole, and micafungin minimum inhibitory concentrations (MICs) were collected from 12 European laboratories for 434 blood isolates, including 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…This suggests a stable and robust intra-laboratory performance of the EUCAST method. The modal MICs obtained in this study were identical to or one dilution from the modal MIC both for the two QC strains also repeatedly tested by Mesquida et al [ 12 ], and for the common Candida species included in recent single and multicentre studies of ibrexafungerp EUCAST susceptibility [ 12 , 13 , 14 ]. These observations suggest a good inter-laboratory agreement.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…This suggests a stable and robust intra-laboratory performance of the EUCAST method. The modal MICs obtained in this study were identical to or one dilution from the modal MIC both for the two QC strains also repeatedly tested by Mesquida et al [ 12 ], and for the common Candida species included in recent single and multicentre studies of ibrexafungerp EUCAST susceptibility [ 12 , 13 , 14 ]. These observations suggest a good inter-laboratory agreement.…”
Section: Discussionsupporting
confidence: 68%
“…Next, the ibrexafungerp MIC distributions were compared to those from three recent publications ( Table 3 ) [ 12 , 13 , 14 ]. All MIC distributions were unimodal with the exception of a bimodal MIC distribution for C. albicans (modes 0.03 and 0.125 mg/L) reported in the multicentre study by Quindos et al [ 14 ], and which therefore was excluded from the WT-UL determination for the aggregated data. The species-specific modal MICs all fell within ± 1 two-fold dilution from the most common species-specific modal MIC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ibrexafungerp is the first triterpenoid class antifungal agent labeled for the treatment of vulvovaginitis [ 111 ]. Although it has been shown that ibrexafungerp displays potent in vitro and in vivo activity against the most clinically relevant species of Candida [ 112 ], so far, no PAFE studies have been published for this new drug. This semi-synthetic derivative of the terpenoid enfumafungin, acts by inhibiting glucan synthase, decreasing 1,3-β-D-glucan polymers and weakening fungal cell wall [ 113 ].…”
Section: Conclusion and Proposals For Further Studiesmentioning
confidence: 99%